Advances in the potential roles of Cullin-RING ligases in regulating autoimmune diseases - Xiaoying Zhang; Xiaoying Zhang; Yu’e Liu; Tong Zhang; Tong Zhang; Yuying Tan; Yuying Tan; Xiangpeng Dai; Xiangpeng Dai; Yong-Guang Yang; Yong-Guang Yang; Yong-Guang Yang; et al. (Frontiers in Immunology, 2023)
Cullin-RING ligases (CRLs) are the largest class of E3 ubiquitin ligases regulating the stability and subsequent activity of a large number of important proteins responsible for the development and progression of various diseases, including autoimmune diseases (AIDs). However, the detailed mechanisms of the pathogenesis of AIDs are complicated and involve multiple signaling pathways. An in-depth understanding of the underlying regulatory mechanisms of the initiation and progression of AIDs will aid in the development of effective therapeutic strategies. CRLs play critical roles in regulating AIDs, partially by affecting the key inflammation-associated pathways such as NF-κB, JAK/STAT, and TGF-β. In this review, we summarize and discuss the potential roles of CRLs in the inflammatory signaling pathways and pathogenesis of AIDs. Furthermore, advances in the development of novel therapeutic strategies for AIDs through targeting CRLs are also highlighted.